If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 1 = 6x + b Reorder the terms: 1 + ax = 6x + b Reorder the terms: 1 + ax = b + 6x Solving 1 + ax = b + 6x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + ax = b + -1 + 6x Combine like terms: 1 + -1 = 0 0 + ax = b + -1 + 6x ax = b + -1 + 6x Reorder the terms: ax = -1 + b + 6x Divide each side by 'x'. a = -1x-1 + bx-1 + 6 Simplifying a = -1x-1 + bx-1 + 6 Reorder the terms: a = 6 + bx-1 + -1x-1
| 3n-6=4+2n | | 14s+2s-4=2+2s | | d(t)=16t^2 | | x+96+x+96=90 | | -4.5x+8.1y=5.4 | | -5(X+2)+2x=5 | | 3x-3=3(x-9) | | -30+5n=8(4n-9) | | -4.5y+8.1x=5.4 | | 5y-1+3y-7=90 | | 5+7c=26 | | 10-6v=-13 | | 7(-5+6p)+7p=-35 | | 0.06x+.08(2x)+.1(3x)=208 | | R-8.8=-8.1 | | 13=8-6m | | 4(8y-2)=-32 | | r=-12(5) | | 126=12(h) | | -4(z+7)-21=2(-2z-6)-37 | | -6(1-4n)=-8(5n-8)-6n | | 4(6x-9)=24x-36 | | 3x+11=-52 | | 12n+9=9+5t | | -34=6(3k+8) | | 19=3j+1 | | (3x-7)(x-3)=-16 | | 28=9x-21x+24 | | 4[2a+3]=-3[a+-1]+31 | | 3(3-x)+4=34 | | 7-8+(-3)+(-5)= | | 840= |